Fourier Transform Infrared (FT -IR) Spectroscopic Studies of Bangladeshi Coals (Chemical Engineering Research Bulletin, 2008)
Fourier transform infrared spectroscopy is widely being used nowadays to characterize both organic and inorganic species of the coal structure. The applications of FT -IR technique for the characterization of coal and minerals have been discussed in this paper. From the FT -IR investigations Bangladeshi coals are revealed as higher rank of bituminous type and minerals are basically silicious nature.Chemical Engineering Research Bulletin 11 (2007) 51-62